O efeito da quantidade de floresta e heterogeneidade da paisagem na polinização de espécies de sub-bosque de mata atlântica - Soares, Raimunda Gomes Silva (Universidade Federal de São Carlos, 2017)
The maintenance of forest areas is one of the most established recommendations for the conservation of biodiversity and key processes in ecosystems, such as pollination. However, this is a challenge that contrasts with the need for anthropic use of natural areas. Among these uses, the growth of agricultural activity on forest areas generates a paradox for conservation. While most crops depend on pollination, maintaining pollination requires the conservation of forest areas. One of the ways to deal with this issue is to analyze the characteristics of the landscape considering the interaction between the amount of forest and other land uses in a more realistic view that includes the function of each use in the maintenance of the ecological process. This study evaluated the effects of forest quantity and landscape heterogeneity on pollination of understory plant species in areas of Atlantic Forest, State of São Paulo, Brazil. Fifteen landscapes of 1 km radius were selected in a forest cover gradient between 21 and 96% and of land use and occupation heterogeneity of 0.18 to 1.67 (Shannon Wiener). Based on the literature we infer the possible contribution of each land use to the conservation of pollinators that forage outside the forest environment. In hexagonal plots of 30m on the side we collected open flowers and recorded the number of flowers in the sampled plant. We counted in fluorescence microscopy the number of pollen grains on the stigma, the number of tubes germinated up to the upper third and to the base of the stylet of each flower. We analyzed 1048 flowers from 189 individuals and 46 species. Pollination varied widely at all levels of the system. In the analyzed landscapes the proportion of forest and heterogeneity of land uses were inversely correlated, requiring a joint analysis of both factors. The higher proportion of forest and lower heterogeneity resulted in increased pollen load, and in the flowers in which at least one pollen tube was formed, the highest number of germinated tubes for each egg (pollination success). The characteristics of the landscape did not influence the germination of pollen, the proportion of pollinated flowers in each plant, nor the pollination success when also considered flowers without pollen tubes. The result of increased pollen grains deposition and pollination success with possible consequences on reproductive success indicates that the proportion of forest in the landscape is an important feature in the conservation of the pollination process of the species studied. We evaluated the quality of pollination in the landscape as moderate, since all variables presented values between 41% and 56% of success. This good result seems to be associated to intermediate to high levels of forest cover and its interaction with a high proportion of uses that provide some type of resource and / or condition for pollinators in all landscapes. This characteristic makes them functionally similar to the sustainability capacity of the pollination function, being also a possible explanation for the absence of effect found in the other analyzed variables. Our study indicates the importance of increasing forest cover associated with good quality land uses in favor of pollination stages.
The effect of forest quantity and landscape heterogeneity of pollination of atlantic rain forest
Keywords: Polinização; Quantidade de floresta; Heterogeneidade da paisagem; Mata Atlântica; Conservação; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA